PERSEPSI DUKUNGAN ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KOMITMEN ORGANISASI PADA PT. GUNUNG PUTRI PERKASA KANTOR CABANG PURWAKARTA - Ela Laela (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
The perception of organizational support and organizational citizenship behavior has a role to increase employee organizational commitment, with perceptions of good organizational support can encourage individual employees to contribute more and give reciprocity by showing organizational citizenship behavior so as to increase employee organizational commitment. The purpose of this study was to analyze and explain the influence of perceptions of organizational support and organizational citizenship behavior on employee organizational commitment. The population in this study were employees of PT. Gunung Putri Perkasa Purwakarta Branch Office. The method of determining the sample used is disproportionate stratified random sampling, with the number of respondents as many as 60 people. The analysis technique used is multiple linear regression analysis. The results showed that the perception of organizational support and organizational citizenship behavior had a positive and significant effect on the organizational commitment of employees at PT. Gunung Putri Perkasa Purwakarta Branch Office. With this research, it is expected that companies can show attention, care, be open, give awards, and create a comfortable working atmosphere.